Changes in traffic crash mortality rates attributed to use of alcohol, or lack of a seat belt, air bag, motorcycle helmet, or bicycle helmet, United States, 1982–2001. Issue 3 (2nd June 2006) - Cummings, P; Rivara, F P; Olson, C M; Smith, K M
Abstract : Objective: To estimate the contributions of five risk factors to changes in US traffic crash mortality: (1) alcohol use by drivers and pedestrians, (2) not wearing a seat belt, (3) lack of an air bag, (4) not wearing a motorcycle helmet, and (5) not wearing a bicycle helmet. Design: Longitudinal study of deaths; attributable deaths were estimated using data from other studies. Setting: US traffic crashes in 1982–2001. Subjects: People who died in a crash. Main outcome measures: Counts of deaths attributed to each risk factor, change in rates of deaths, and counts of lives saved by changes in risk factor prevalence. Results: There were 858 741 traffic deaths during the 20 year period. Estimated deaths attributed to each factor were: (1) alcohol use, 366 606; (2) not wearing a seat belt, 259 239; (3) lack of an air bag, 31 377; (4) no motorcycle helmet, 12 095; (5) no bicycle helmet, 10 552. Over the 20 years, mortality rates attributed to each risk factor declined: alcohol by 53%; not wearing a seat belt by 49%; lack of an air bag by 17%; no motorcycle helmet by 74%; no bicycle helmet by 39%. There were 153 168 lives saved by decreased drinking and driving, 129 297 by increased use of seat belts, 4305 by increased air bag prevalence, 6475 by increased use of motorcycle helmets, and 239 by increased use of bicycle helmets. Conclusions: Decreased alcohol use and increased use of seat belts were associated with substantial reductions in crash mortality from 1982 through 2001. Increased presence of air bags, motorcycle helmets, and bicycle helmets were associated with smaller reductions.